The Implementation Of Inquiry-Based Learning In Teaching Writing At The First Year Of SMA Negeri 1 Gemolong, Sragen - MUDRIKAH , ANDRIYANI (2012)
The study is aimed at describing 1) the implementation of Inquiry-based Learning consisting the objective of teaching writing, material of teaching and classroom activity, and 2) problem faced by the teacher in teaching writing using Inquiry-based Learning at the first year of SMA Negeri 1 Gemolong, Sragen. The writer gets the data of the research from event, informant and document. The techniques collecting data are observation and interview about teaching writing using Inquiry-based Learning. The research finding shows that Inquiry-based Learning is the best and appropriate learning that can be used to develop students' motivation in writing especially in writing descriptive text for the first year student of SMA Negeri 1 Gemolong, Sragen. The objective of teaching writing at the first year students of Senior High School is to enable students to express their ideas in the form of written language. The teaching materials can be many sources. The teacher not only takes the material from the English textbooks but also he uses teacher-made materials. The classroom activities are appropriate with the procedure of Inquiry-based Learning, consisting three stages exploration, elaboration and confirmation. The teacher has several problems in teaching writing namely difficulty in improving students' vocabulary, limitation of time and lacking of teaching media.